Middle School Students and Graduate Students as Web Information Seekers - Bilal, Dania; Kirby, Joe (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study investigated the information-seeking behavior of middle school students and graduate students in using the Yahooligans! Web search engine/directory to find the correct answer to a fact-finding search task. It analyzed and compared the overall patterns of both student groups' Web traversal behaviors, including searching moves, browsing moves, backtracking moves, looping moves, target location and deviation moves, and the...